Xuan Ye. - LAI, OPHELIA (ArtAsiaPacific)
The article offers information on artist Xuan Ye and her works in digital media art, discussing her website art "IN BETWEEN () WE OSCILLATE," her web-application based installation series "EveryLetterCyborg," and the inspiration she gets from object-oriented programming.